Adsorption of ethanol onto phenol resin based adsorbents for developing next generation cooling systems. (February 2015) - El-Sharkawy, Ibrahim I.; Uddin, Kutub; Miyazaki, Takahiko; Baran Saha, Bidyut; Koyama, Shigeru; Kil, Hyun-Sig; Yoon, Seong-Ho; Miyawaki, Jin
Graphical abstract: Abstract: Adsorption characteristics of ethanol onto two promising adsorbents have been investigated for developing high performance adsorption chillers. These new adsorbents are based on spherical phenol resin treated with different mass ratios of KOH named as KOH4-PR and KOH6-PR. Experimental adsorption isotherm measurements show that the adsorption capacity of KOH4-PR/ethanol is as high as 1.43 kg kg −1 whilst one kg of KOH6-PR able to adsorb nearly about 2 kg of ethanol. To the best of our knowledge, the studied adsorbents possess the highest ethanol uptake. Moreover, it is found that the KOH4-PR/ethanol pair has notably high adsorption kinetics at the lower range of adsorption temperatures. Experimental measurements of adsorption uptake and adsorption uptake rate of the studied pairs have been analyzed and isosteric heats of adsorption have also been extracted.